Optimality Conditions for Fractional Variational Problems with Dependence on a Combined Caputo Derivative of Variable Order - Tavares, Dina (2018)
We establish necessary optimality conditions for variational problems with a Lagrangian depending on a combined Caputo derivative of variable fractional order. The endpoint of the integral is free, and thus transversality conditions are proved. Several particular cases are considered illustrating the new results.